Explorations in Baltic medical history, 1850-2015 - Hansson, Nils 1983-; Wistrand, Jonatan 1980- (Rochester studies in medical history, 2019)
Examines medical history in northern Europe from 1850 to 2015 and sheds new light on the circulation of medical knowledge in that region